Correlation between Students’ Risk-Taking Behavior and Students’ Listening Comprehension - Ade Safrinal; Desi Surlitasari Dewi; Aulia Putri (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2016)
Teachers of second language, should be aware of who their students really are. It means that teachers must comprehend diversities among their students in term of many kinds of personality traits and their links with second language skills. This study is aimed to find out the correlation between students’ risk taking behavior and their listening comprehension at fourth semester students of English Department Universitas Riau Kepulauan in the academic year of 2015/2016. The study is done with quantitative procedure by using students’ risk taking and listening comprehension’s score to obtain the correlation between both of the variables. The finding of the research is that rcalculated(-0.065) is lower than rtable(0.456). It means that null hypothesis is accepted and alternative hypothesis is rejected. The finding of the study concluded that there is no correlation between students’ risk taking and students’ listening comprehension. Teachers can use this result as starting point to find the correlation between those variables and other variables in order to help the students in achieving better result in second language learning.Keywords: correlation study, risk taking and listening comprehension